2020
DOI: 10.1111/tmi.13497
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey of the availability and affordability of asthma and COPD medicines in Nigeria

Abstract: objective(s) To determine the availability and affordability of asthma and COPD medicines across Nigeria. methods This was a cross-sectional survey conducted in 128 pharmacies (51 in public sector hospitals, 51 private sector community pharmacies and 26 charity or big private hospitals) across the six geopolitical zones of Nigeria using the WHO/Health Action Initiative method. The proportion of pharmacies where medicines were available, the median retail prices of originator and generics and affordability were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…The barriers for the implementation of the EML are similar to the EDL barriers reported above, and the main barriers were poor financial access 39,48,78,79,83,[86][87][88][89]104,110,136,[140][141][142][143][144][145][146][147][148][149] , poor geographical access 36,65,74,82,104,143,146,150 and health facility access 73,74,106,[150][151][152] .…”
Section: Accessibility Of Carementioning
confidence: 82%
See 2 more Smart Citations
“…The barriers for the implementation of the EML are similar to the EDL barriers reported above, and the main barriers were poor financial access 39,48,78,79,83,[86][87][88][89]104,110,136,[140][141][142][143][144][145][146][147][148][149] , poor geographical access 36,65,74,82,104,143,146,150 and health facility access 73,74,106,[150][151][152] .…”
Section: Accessibility Of Carementioning
confidence: 82%
“…The enabler themes for the EDL implementation are opposite to the EDL barriers mentioned above 113,114,115, 103. The EML enablers are opposite of the EML barriers reported above, and mainly included availability of essential medicines in facilities 34,37,48,[57][58][59]66,87,92,108, , and adequate capacity of facilities to provide care 34,138 .…”
Section: Health Systems-level Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, as of many LMICs, health-service factors such as poor awareness and knowledge among physicians regarding asthma guidelines, suboptimal infrastructure and diagnostic facilities, and non-availability and high cost of asthma medications were associated with poor asthma control. [10,27] In fact, we found that the use of diagnostic tools for asthma diagnosis and management was very low since only 15.7% of patients had undergone peak flow meter measurement and only 12.4% were diagnosed for asthma using spirometry. Lung function assessment is recommended in asthma care and underuse of these tools has been associated with undertreatment of asthma and poor asthma control.…”
Section: Discussionmentioning
confidence: 98%
“…More so, limited access to essential asthma medicines, due to non-availability and high cost, contributes to poor medication adherence. [8][9][10] In this issue of the Journal of the Pan African Thoracic Society, Osman et al reported that nearly 85% of patients attending asthma clinics in Sudan were poorly controlled with patient, physician, health system, and social factors contributing to poor asthma control. [5] This figure is comparable to what was reported in AIRNIG and another study.…”
mentioning
confidence: 99%